Study the Spectral Properties of Coumarine -47 Dissolved in Chloroform - Baghdad Science Journal (مجلة بغداد للعلوم)
The spectral propetties (absorption and fluorescence) of Coumarine-47 laser dye have been studied. This type of laser dye belong the Coumarine family and it has dissolved in chloroform at different concentrations (1x10-5, 5x10-5, and 1x10-4 M) at room temperature. The achieved results have been pointed out to increase in the absorption and fluorescence as the concentration increased which are agreements with Beer – Lambert law. These have been also showed an expansion in the spectral range of absorption and fluorescence with a noticed shift in the direction of longer wavelength (Red-shift) with increasing concentration. The quantum efficiency of the dissolved C47 in chloroform has been computed by using the brevious concentrations and their results are as follows (69%, 63%, and 45%) respectively. The radiative and fluorescence lifetime have been also computed as given (6.47ns, 4.67ns, and 2.06ns) and (4,07ns, 3.22ns, and 1.47ns) respectively.